The Effect of Perceptual-Motor Exercises on the Neuropsychological Skills of Children with Visual Impairment: A Single-Subject Study - Zinat Tavakoli; Maryam Nezakt-Alhosseini; Salar Faramarzi; Sheila Safavi-Homami (Vesnu Publications, 2020)
Introduction: The purpose of the present study is to investigate the effect of perceptual-motor training on neuropsychological skills in children with visual impairment.Materials and Methods: A single-case experimental study was conducted on three children (2 boys and 1 girl, aged between 4 and 7 years old) with visual impairment (20/70 and 20/200) who referred to Department of Social Welfare of Isfahan, Iran. The participants were selected through convenience purposive sampling method for the perceptual-motor training. The Language Development Scale, Guzel perceptual-motor Scale, Stanford-Binet scale, and Conner's Neuropsychological questionnaire were used to collect the data. The multiple baseline design (MBA) was used in the present study, followed by the perceptual-motor intervention. The baseline position for the first, second, and third participants lasted three, five, and seven weeks, respectively, and the intervention duration for each participant was eight weeks as three sessions per week with each session lasting for one hour. Exit of the participants according to their entry into the training program was made in the step by step manner. The data were plotted and then the stability envelope and the trend of all three participants in the baseline and intervention positions were plotted and compared.Results: The perceptual-motor training was effective on neuropsychological skills [percentage of non-overlapping data (PND) = 87.5%] in three participants.Conclusion: The perceptual-motor exercise may be an appropriate training method to improve neuropsychological skills in children with visual impairment.